Jejak Raden Jaka Prabangkara pada Kerajaan Majapahit Abad ke-15 M dalam Babad Jaka Tingkir - Tatit Lestari; Rizki Endi Septiyani; Annisa R. Isyanti; Septi D.N. Aini; Bagus W. Pratama; Rudi T. Laksono; Imron Imron (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
Raden Jaka Prabangkara was the son of Brawijaya V, the last king of the Majapahit Kingdom. He was the king's son of an ordinary woman or concubine. During the reign of his father, which was around the 15th century, Raden Jaka Prabangkara had the role as a village chief in Sungging area. Besides, he was also given the task to become a palace painter because of his expertise in painting. This study aims to describe the traces of Raden Jaka Prabangkara's life during the reign of Majapahit Kingdom in the 15th century and the lessons that can be learned from the stories in Babad Jaka Tingkir. This study uses qualitative research method based on the literature review in the book of Babad Jaka Tingkir: Babad Pajang written by Sastronaryatmo (2011) which has been translated into Indonesian. The results of this study are (1) The background story of the birth of Raden Jaka Prabangkara in Babad Jaka Tingkir, (2) The role of Raden Jaka Prabangkara in the 15th century during the reign of Majapahit Kingdom in Babad Jaka Tingkir, (3) The chronology of the seclusion of Raden Jaka Prabangkara to China in Babad Jaka Tingkir, (4) The wisdom that can be learned from Raden Jaka Prabangkara's life. Overall, it can be seen that there are traces of Raden Jaka Prabangkara's life journey during the reign of Majapahit kingdom in 15th century based on the book of Babad Jaka Tingkir.